COMPARATIVE ANALYSIS OF THE FATTY ACID COMPOSITION OF MILK FROM RED STEPPE COWS IN DIFFERENT CLIMATIC ZONES OF THE NORTH CAUCASUS - Sergey A. Oleinik; Valentin S. Skripkin; Artem V. Lesnyak; Olga V. Sycheva; Evgeny N. Chernobai (Siberian Journal of Life Sciences and Agriculture, 2023)
Dairy cattle of the red steppe breed are adapted to arid conditions, have high adaptive qualities and are still in demand for breeding in agricultural organizations. The article describes the characteristics of the population of cows of the red steppe breed according to the main indicators of milk quality in the farms of the Stavropol Territory. The mass fraction of fat and protein, the amount of fatty acids in milk, as well as the correlation coefficients between milk indicators and paratypical factors were determined. The research results have shown that milk corresponds to the breed characteristics characteristic of this breed of cows. The average annual dairy productivity of a herd of cows located on the border of the northeastern slope of the Stavropol Upland and the southwestern part of the Manych Lowland (n = 380-430 heads, herd I) is 4.0-4.3 thousand kg/head, and a herd of cows located in the northeastern part of the steppe plain of the Stavropol Territory (n = 600-636, herd II), respectively, the milk productivity is 4.1-4.4 thousand kg / head of milk. The average annual fat content in milk in cows was in the range of 4.08-4.45%, while in cows of the II herd this indicator was higher by 9.5%. The average annual protein content in milk, respectively, was at the level of 3.32-3.63%, while in cows in the II herd this indicator was higher by 9.2%. The percentage ratio of unsaturated to saturated fatty acids was 44,9% in cows in the II herd and 58% in cows in the I stad.